Actin dynamics regulate proteasome homeostasis. Issue 5 (27th May 2022) - Williams, Thomas; Rousseau, Adrien
Abstract : Cells require thousands of unique proteins to be in the right place, at the right time, in the right amounts and with the right modifications. They do this through several processes collectively known as protein homeostasis. TORC1 is a principal regulator of protein homeostasis, coordinating protein synthesis and degradation. The proteasome, composed of a core particle and one or two regulatory particles, degrades unwanted protein. Diverse stresses cause a protein homeostasis imbalance: inhibiting TORC1 and the misfolded/damaged protein load. Following TORC1 inhibition, proteasome regulatory particle assembly chaperone (RPAC) translation is increased and thus cells assemble more proteasomes to degrade the damaged and misfolded proteins, thereby restoring protein homeostasis. Using yeast, we identify an endocytic protein, Ede1, that interacts with and is critical for translation of RPAC mRNA following TORC1 inhibition. We find two further endocytic proteins important for RPAC translation regulation. Mutants of these proteins cause altered Arp2/3 activity, and hence altered formation of actin patches/endocytic sites. We show that RPAC mRNA is transported on actin cables and interacts with actin patches. TORC1 inhibition depolarises the actin cytoskeleton, causing RPAC mRNA accumulation on actin patches concurrent with translation. We demonstrate Ede1 is essential for RPAC mRNA localisation regulation following rapamycin treatment. This work shows that, upon actin depolarisation, RPAC mRNA is recruited to actin patches, likely by Ede1, and translation occurs. Actin regulation is therefore a key element of proteasome (and therefore protein) homeostasis.